2010
DOI: 10.1016/j.tins.2010.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The sticky issue of neurosteroids and GABAA receptors

Abstract: Endogenous neurosteroids and their synthetic analogs (neuroactive steroids) are potent modulators of GABA A receptors. Thus, they are of physiological and clinical relevance for their ability to modulate inhibitory function in the central nervous system. Despite their importance, fundamental issues of neurosteroid actions remain unresolved. Recent evidence suggests that glutamatergic principal neurons, rather than glia, are major sources of neurosteroid synthesis. Other recent studies have identified putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
97
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 73 publications
9
97
0
1
Order By: Relevance
“…It is now well recognized that progesterone and its metabolites are potent allosteric modulators of GABA A R function through a direct, nongenomic interaction with specific receptor subtypes, being the dcontaining receptor especially sensitive to them [27]. However, fluctuations in the concentration of neuroactive steroids affect not only GABA A R function but also the expression of receptor subunits [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is now well recognized that progesterone and its metabolites are potent allosteric modulators of GABA A R function through a direct, nongenomic interaction with specific receptor subtypes, being the dcontaining receptor especially sensitive to them [27]. However, fluctuations in the concentration of neuroactive steroids affect not only GABA A R function but also the expression of receptor subunits [6].…”
Section: Discussionmentioning
confidence: 99%
“…The potentiating effect of neurosteroids can be mediated by steroid interactions with its site within the same β-α pair that mediates receptor activation as well as the opposite β-α pair [179]. Chisary et al [180] have shown that neurosteroids require a membranous route of access to transmembrane-domain binding sites that might have implications for the design of novel neuroactive steroids because their lipid solubility and related accessibility are probably the key determinants of receptor modulation [180]. This also suggests that by virtue of their high lipid solubility, µM concentrations of neurosteroids may be achieved locally [31].…”
Section: G-protein-coupled Receptors Via Nongenomic Mechanisms Inclumentioning
confidence: 99%
“…To do this, we exploited the micropipette aspiration technique (MAT), concentrating on giant unilamellar vesicle (GUV) model systems. The neurosteroids that we concentrated on are allopregnanolone (in the following Allo), an endogenous highly lipophilic molecule [20], known to modulate GABA A receptor activity [21,22] and one of its isoform isoallopregnanolone (in the following isoAllo). In particular, Allo potentiates GABA-evoked currents mediated by GABA A receptor activation at low nanomolar concentrations and is able by itself to activate the GABA A receptor at higher concentrations [23].…”
Section: Introductionmentioning
confidence: 99%